2015
DOI: 10.1016/j.ejrh.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impacts of climate change and crop land use change on streamflow, nitrates and phosphorus: A modeling study in Bavaria

Abstract: a b s t r a c tStudy region: Bavaria, Germany. Study focus: The Altmühl River is prone to nutrient inputs from agricultural activities. Quantifying nitrate nitrogen (NO 3 − -N) and total phosphorus (TP) concentrations due to potential future changes in the watershed is necessary for managing water quality and adhering to water policy directives. The Soil and Water Assessment Tool (SWAT) was used to provide stakeholders with support in determining the impacts of climate change (CC) in combination with crop land… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 61 publications
(59 reference statements)
1
37
0
Order By: Relevance
“…The uncertainty is quantified by the 95% confidence intervals, the interquantile ranges, the percentiles, and the total spread of the monthly variables. The evaluation of the future nutrient loads in the Altmühl per se has already been presented in Mehdi et al (2015Mehdi et al ( , 2016.…”
Section: Combined Uncertainties Of Climate Change Impacts On Hydrologymentioning
confidence: 99%
See 1 more Smart Citation
“…The uncertainty is quantified by the 95% confidence intervals, the interquantile ranges, the percentiles, and the total spread of the monthly variables. The evaluation of the future nutrient loads in the Altmühl per se has already been presented in Mehdi et al (2015Mehdi et al ( , 2016.…”
Section: Combined Uncertainties Of Climate Change Impacts On Hydrologymentioning
confidence: 99%
“…Observed daily flows at the Thann (1981Thann ( -2010, Aha (1975Aha ( -2010 and Treuchtlingen (1948Treuchtlingen ( -2006 More detailed information on the model set-up for the Altmühl watershed is described in Mehdi et al (2015).…”
Section: The Hydrological Model Swatmentioning
confidence: 99%
“…Nearly all studies have shown that climate change is likely to have a significant impact on contaminants' loads. Most indicate an overall increase in contaminants loads [8][9][10][11][12][13][14][15][16]. It is obvious that this increase corresponds to water flow augmentation driven by precipitation increase.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al, 2015) and scenarios that reflect hypothetical shifts between various percentages of urban, forest, agricultural and other land use (Zhang et al, 2015(Zhang et al, , 2016Wu et al, 2015). Similar types of combined SWAT climate change/land use change studies have been performed in other regions including Asia (Sayasane et al, 2015;Singkran et al, 2015;Tan et al, 2015), Europe (Serpa et al, 2015;Mehdi et al, 2015b;Guse et al, 2015) and North America (Mehdi et al, 2015a;Neupane and Kumar, 2015;Goldstein and Tarhule, 2015).…”
Section: Introductionmentioning
confidence: 99%